Planting trees, planting hope: an analysis of the role of urban forestry in addressing environmental inequality in Cape Town - Gauld, Zoë (Department of Social Development, 2015)
The presence of trees in urban spaces has been identified as providing numerous environmental, psychosocial, and economic benefits. However, rather than being an equally distributed resource which all city residents share, tree cover in Cape Town, South Africa tends to be a marker of environmental inequality and racism, with trees being significantly more prevalent in wealthy, predominantly white, areas as opposed to poor, predominantly black, ones. The present study aims to analyse the potential for urban forestry to address this inequality. In order to gain in-depth understanding, a case study of an urban forestry project at the Lathi-Tha School of Skills in Khayelitsha is conducted. Within this framework, semi-structured and photoelicitation interviews are undertaken with 5 learners and 4 staff members in order to determine participants’ experiences and perceptions of their urban forestry project. The findings suggest that urban forestry does have the ability to redistribute the environmental, economic, and psychosocial benefits of tree cover to poor communities. Additionally, participation in urban forestry in South Africa is shown to have the capacity to tackle social inequalities that continue to recreate green-space inequality.